2013
DOI: 10.1177/2047487313490257
|View full text |Cite
|
Sign up to set email alerts
|

Frailty is independently associated with 1-year mortality for elderly patients with non-ST-segment elevation myocardial infarction

Abstract: Frailty is independently associated with 1-year mortality for elderly patients with non-ST-segment elevation myocardial infarction, 2014, European Journal of Preventive Cardiology, (21) For the large population of elderly patients with cardiovascular disease, it is crucial to identify clinically relevant measures of biological age and their contribution to risk. Frailty is denoting decreased physiological reserves and increased vulnerability. We analyzed the manner in which the variable frailty is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 36 publications
4
85
1
3
Order By: Relevance
“…Although we did measure comorbidities that are not typically collected in large cardiovascular studies (e.g., malignancies, psychiatric, and neurological disorders), it is highly possible that other nonmeasured parameters such as frailty status, postdischarge management, and lifestyle issues have much stronger influence on long-term mortality in older compared to younger patients with AMI [7,36].…”
Section: Discussionmentioning
confidence: 96%
“…Although we did measure comorbidities that are not typically collected in large cardiovascular studies (e.g., malignancies, psychiatric, and neurological disorders), it is highly possible that other nonmeasured parameters such as frailty status, postdischarge management, and lifestyle issues have much stronger influence on long-term mortality in older compared to younger patients with AMI [7,36].…”
Section: Discussionmentioning
confidence: 96%
“…Most studies on ACS based frailty assessment on retrospective review of medical files [12-14] instead of direct estimation of a frail phenotype. Sujino et al [15] conducted a prospective study in patients ≥85 years admitted with STEMI, exploring predictors of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Skeletal muscle weakness is one of the phenotypes of frailty 4 and is strongly associated with reduced exercise capacity 5,6 and physical disability. 7 Recent studies have indicated that skeletal muscle strength is a prognostic factor in community-dwelling individuals, [8][9][10] chronic heart failure, 11,12 and in different patient populations.…”
Section: Introductionmentioning
confidence: 99%